Surface Roughness and Electrical Resistivity of High-purity Zinc Irradiated with Nd:YAG Laser Pulses. (2015) - Butt, M.Z.; Ali, Dilawar; Tanveer, M. Usman; Naseem, S.
Abstract: Six specimens of 99.995% pure zinc in the form of strips (15 mm × 8 mm × 0.5 mm) were irradiated with Q-switched pulsed Nd:YAG laser (λ=532nm, E =50 mJ, τ =6 ns, repetition rate=10 Hz) in vacuum∼10 -3 Torr. The specimens were irradiated with 50, 60, 70, 80, 90 and 100 laser shots; the laser fluence and laser intensity at the irradiation spot were 4.24 J/cm 2 and 7.07 × 10 8 W/cm 2, respectively. Scanning electron microscope (SEM) examination of laser irradiated specimens revealed different features, e.g. wavelike structures, ridges, dips, micro cones, cavities, nano and micro size droplets, as well as solid flakes, etc. on the surface. These features are a result of splashing, hydrodynamic and exfoliational sputtering. Average surface roughness was measured from SEM micrographs using Nanotec software WSxM 5.0 develop 1.1. The electrical resistivity was determined by four- point probe technique. It is observed that average surface roughness and electrical resistivity vary with the number of laser shots in an identical manner, and are therefore found to be directly related to each other.